How Senior Executives Think and Work: Implications for the Design of Executive Information Systems - Keane, David (School of Management Working Papers, 1991)
How do senior executives think ? Where do they get their information from ? What strategies do they use in learning about their organisational environments ? Which information media do they prefer to use ? Finding answers to these questions is fundamental in helping us understand how to build Executive Information Systems (EIS). This paper reviews the literature on senior executive work and decision making before presenting some practical guidelines for the design and implementation of high level executive information systems.